2022
DOI: 10.3390/polym14122435
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Poly(lactic acid) and Silk Fibroin Based Nanofibrous Scaffold for Meniscus Tissue Engineering

Abstract: Biopolymer based scaffolds are commonly considered as suitable materials for medical application. Poly(lactic acid) (PLA) is one of the most popular polymers that has been used as a bioscaffold, but it has poor cell adhesion and slowly degrades in an in vitro environment. In this study, silk fibroin (SF) was selected to improve cell adhesion and degradability of electrospun PLA. In order to fabricate a PLA/SF scaffold that offered both biological and mechanical properties, related parameters such as solution v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…Instead, silk fibroin polymer spontaneously formed higher molecular complexes that localize between PLA microfibers. This has also been observed in a study [ 35 ] where directly electrospun PLA/silk fibroin nanofibrous scaffolds confirmed the intrinsic ability of silk fibroin to form complexes. In Supplemental AVI Files (Video S1a–c) , 3D fluorescent analysis of PLA scaffolds at 20× magnification, in 100 µm depth of scan, clearly shows the different densities and localization of LSCs related to PLA modifications.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Instead, silk fibroin polymer spontaneously formed higher molecular complexes that localize between PLA microfibers. This has also been observed in a study [ 35 ] where directly electrospun PLA/silk fibroin nanofibrous scaffolds confirmed the intrinsic ability of silk fibroin to form complexes. In Supplemental AVI Files (Video S1a–c) , 3D fluorescent analysis of PLA scaffolds at 20× magnification, in 100 µm depth of scan, clearly shows the different densities and localization of LSCs related to PLA modifications.…”
Section: Resultssupporting
confidence: 83%
“…Both silk fibroin and gelatin are successfully fabricated into biomedical scaffolds based on solution electrospinning. For example, silk fibroin was combined with PLA for the development of a biomimetic meniscus scaffold [ 35 ], or gelatin was blended with chitosan for the in vitro study of human dermal fibroblast cells culture for the application in skin tissue engineering [ 36 ]. Other tissue engineering applications include bone [ 37 ], nerve [ 38 ], vascular [ 39 ], and tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…The adhesion and proliferation of MSCs could be enhanced on a moderately hydrophilic surface (water contact angle of 40–80°) [ 47 ]. However, PLA is a typical hydrophobic polymeric material that lacks cell recognition signals and has limited applications in biomaterials [ 48 ]. The structure of poly(dopamine) contains a large number of phenolic hydroxyl and amino functional groups, and the introduction of poly(dopamine) to PLA scaffolds can effectively improve hydrophilicity and bioactivity.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 (d). The printed cubes were mechanically tested as soon as possible after the printing process, since PLA is degradable in an in vitro environment, although the degradation is very slow ( Promnil et al., 2022 ). There was a one-day gap between the printing of the cubes and the beginning of the support material removal process and a half-day gap between the support material removal process and mechanical testing.…”
Section: Methodsmentioning
confidence: 99%